Induction therapy with linezolid/clarithromycin combination for Mycobacterium chelonae skin infections in immunocompromised hosts. (11th February 2015) - Parize, P.; Hamelin, A.; Veziris, N.; Morand, P.C.; Guillemain, R.; Lortholary, O.; Dupin, N.
Abstract: Background: The optimal management of Mycobacterium chelonae disease in immunocompromised patients remains unclear. A combination of antimicrobial agents is recommended as monotherapy with clarithromycin has been associated with clinical failures due to acquired resistance. Objectives: We aim to report the efficacy and tolerability of linezolid in association with clarithromycin for the treatment of M. chelonae infections in immunocompromised patients. Methods: We describe four immunocompromised patients treated by linezolid and clarithromycin for cutaneous M. chelonae disease. Results: This combination was associated with rapid clinical efficacy in all patients with no relapse observed after a median follow‐up of 2.25 years (1.4 years). However, this treatment was responsible for frequent adverse events including thrombocytopaenia, myalgia and mitochondrial toxicity. All adverse effects were reversible after linezolid discontinuation. Conclusions: We therefore suggest linezolid/clarithromycin combination as the initial therapeutic strategy for M. chelonae skin infections in immunocompromised patients.